Long-term effects of early stress due to earthquake exposure on depression symptoms in adulthood: a cross-sectional study - Lu, Wen-Ting; Zhao, Xiao-Chuan; Wang, Ran; Li, Na; Song, Mei; Wang, Lan; Yu, Lu-Lu; Gao, Yuan-Yuan; Wang, Yu-Mei; An, Cui-Xia; Wang, Xue-Yi (Injury, 2023)
This study aimed to investigate the long-term effects of early stress by Tangshan earthquake on symptoms of depression in adulthood. A total of 1534 volunteers born and raised in Tangshan were investigated; finally, 1328 subjects were enrolled in the study. They were divided into three groups according to their birth dates: infant exposure, prenatal exposure, and non-exposure. The questionnaires and psychological evaluation of all subjects were completed using a one-on-one psychological test. The rate of depressive symptoms in the prenatal exposure group was the highest, and the lowest in the non-exposure group, with statistical differences among the three groups (P = 0.002). Moreover, the incidences of depressed mood, suicide ideation and work and loss of interest in the prenatal exposure group were significantly higher than those in the infant exposure group and the non-exposure group (P = 0.008, P = 0.001, P = 0.038, respectively). Multiple logistic regression analysis showed that male could be a protective factor for symptoms of depression in adulthood, and earthquake exposure was an important predictor of the incidence of depression symptoms. Fetal or infancy exposure to earthquake might correlate to depression symptoms in adulthood.